Molecular Characterization of Foot-and-Mouth Disease Virus Type C of Indian Origin - Nagendrakumar, Singanallur Balasubramanian (American Society for Microbiology, 2005)
Comparison of nucleotide sequences of the partial 1D region of foot-and-mouth disease type C viruses of Indian origin with those of European, South American, and Southeast Asian viruses revealed that the Indian viruses form a distinct genotype. The vaccine strain C IND/51/79 belongs to this genotype and may be a prototype strain of this genotype.